Evaluation of ash‐free coal for chemical looping combustion ‐ part II: Thermogravimetric multi‐cycle performance. (10th November 2016) - Shabani, Azar; Rahman, Moshfiqur; Pudasainee, Deepak; Samanta, Arunkumar; Sarkar, Partha; Gupta, Rajender
Abstract : In this paper, performance of AFC in CLC during multi‐cycle thermogravimetric (TG) experiments was investigated. The close to stoichiometric CuO/AFC ratio of 30 is selected for the consecutive reduction and re‐oxidation cyclic experiments. The reactivity of the first cycle was higher than the consecutive cycles due to the fresh CuO in the first cycle. The thermal behaviours, such as mass change in the consecutive cycles, were almost similar and there was no residual ash deposition after each cycle. Furthermore, reduction and oxidation processes were performed with different isothermal times. After 1 h the combustion was incomplete but a longer combustion period (3 h) leads to almost complete combustion. Moreover, fresh samples and solid residues were analyzed by several advanced analytical techniques including XRD, SEM, and BET. XRD analysis of the residue of CuO/AFC showed the presence of CuO at the end of the cycles; CuO and SiO2 in residues from CuO/BL raw coal (parent coal of AFC) were shown in XRD results. At the higher temperatures (900 °C) the sintering effect and increased agglomeration were observed after each cycle. Total pore volume and average pore radius of the material decreased, however, the CLC performances at 900 °C did not reduce. The multi‐cycle experiments showed AFC as a promising candidate for CLC.